PENGEMBANGAN MODEL BIAYA KEMACETAN BAGI PENGGUNA MOBIL PRIBADI DI DAERAH PUSAT PERKOTAAN YOGYAKARTA - Sugiyanto, Gito; Munawar, Ahmad; Malkhamah, Siti; Sutomo, Heru (Jurnal Transportasi, 2011)
Traffic congestion on the road occurred when travel demand exceeds the capacity of the road. This study aims to estimate and develop a model of congestion costs for private car users in the area of Jalan Malioboro, Yogyakarta, with a length of 1.414 km. The study was limited to the congestion charge for private car users only. The results show that the generalized cost of private car transportation on the actual conditions in the Malioboro area, Yogyakarta, is Rp. 5,513.77 per trip and on the conditions of free flow speed is Rp. 2,598.78 per trip, so that the congestion charge for private car users in this region is Rp. 2,914.99 per trip. The form of congestion charge model for private car users in the area of Malioboro, Yogyakarta, is an exponential function, with the lower the actual traffic speed, the greater the cost of traffic congestion caused.Keywords: congestion charge, private car, the combined cost of transportation, vehicle operating costs,the cost of travel time.